Express waterproof bag and preparation method thereof
By using a combination of degradable materials and nanomaterials, the degradability and waterproof performance of express waterproof bags are improved, and the environmental pollution problems caused by traditional plastic materials are solved, and the balance between stability and environmental friendliness in use is achieved.
Patent Information
- Application Number
- CN202510204363.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-04-29
AI Technical Summary
The existing express waterproof bags use traditional plastic materials, resulting in poor degradability and insufficient environmental friendliness, causing environmental pollution.
Degradable materials such as polylactic acid (PLA), polyadipate-butylene terephthalate (PBAT) and polyhydroxy fatty acid esters (PHA) are used to combine nanocellulose, modified montmorillonite, photosensitizers and biological enzyme catalysts to improve the degradability and waterproofing properties of the materials through blending and hot pressing treatment.
It significantly improves the biodegradability and waterproof performance of express waterproof bags, ensures sufficient strength during use, and quickly degrades after being discarded, reducing environmental pollution.
Smart Images

Figure BDA0005284093680000111 
Figure BDA0005284093680000121 
Figure BDA0005284093680000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging, and in particular to an express waterproof bag and a preparation method thereof. Background Art
[0002] With the booming development of e-commerce, the demand for express parcel delivery is increasing. How to ensure the safety and integrity of express parcels during transportation has become an urgent problem to be solved. As a packaging material, express waterproof bags are widely used to protect parcels. Its main purpose is to protect parcels from external environmental factors by providing waterproof, tear-resistant and wear-resistant functions, especially against rain, moisture and wear and tear that may be encountered during transportation. The use of waterproof bags can not only improve logistics efficiency, but also reduce parcel damage caused by environmental factors, thereby improving customer experience and reducing transportation losses.
[0003] Existing express waterproof bags usually use traditional plastic materials (polyethylene or polypropylene), which have certain waterproof functions, but have great deficiencies in terms of degradability and environmental friendliness. Traditional plastic bags take a long time to degrade in the environment, and may release harmful substances during the degradation process, causing environmental pollution. Especially after large-scale use, plastic waste has accumulated, bringing great pressure to the ecological environment. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an express waterproof bag and a preparation method thereof, which solve the problems of poor degradability and insufficient environmental friendliness of the existing express waterproof bags when using traditional plastic materials.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a waterproof express bag, comprising the following mass ratio components: Polylactic acid: 60-70 parts Polylactic acid (PLA): PLA is a biodegradable bio-based material with good mechanical properties and biodegradability, but it is very brittle. By blending with PBAT and PHA, the brittleness of PLA can be optimized, and its toughness and operability can be improved. The mechanism of PLA degradation is to decompose it into low molecular weight products through hydrolysis reaction, and finally degrade into carbon dioxide and water.
[0006] Polybutylene adipate-terephthalate: 20-30 parts Polybutylene adipate-terephthalate (PBAT): PBAT is a degradable polyester material with good flexibility, which can effectively improve the brittleness of PLA. PBAT has good biodegradability and can be degraded quickly in the natural environment. PBAT degrades through ring-opening hydrolysis reaction, and the degradation process has a long chain segment breakage process, which increases the controllability of its degradation.
[0007] Polyhydroxyalkanoate: 5-10 parts Polyhydroxyalkanoate (PHA): PHA is a biodegradable material with strong biocompatibility and fast degradation rate. The mechanism of PHA is to decompose through hydrolysis and microbial degradation. The ester bond breaks and short-chain fatty acids are generated during the degradation process, which is harmless to the environment. Its main function is to accelerate the degradation rate of the overall material, so that the express bag can be degraded faster after use.
[0008] Nanocellulose: 2-5 parts Modified montmorillonite: 1-3 parts Nanocellulose (CNF) and modified montmorillonite (MMT): Both materials have a high specific surface area and can significantly enhance the mechanical and waterproof properties of the substrate. Nanocellulose enhances its compatibility with the substrate through surface modification, which can improve the tensile strength and durability of the film. Modified montmorillonite can improve the barrier properties of the material by forming a nano-scale dispersion in the polymer material, especially playing an important role in water resistance and moisture resistance. The composite effect of the two can enhance the structural integrity of the material and improve its waterproof performance.
[0009] Photosensitizer: 0.5-1.5 parts Bio-enzyme catalyst: 0.25-0.5 parts Plasticizer: 0.5 to 1 part.
[0010] Preferably, the photosensitizer comprises one of benzophenone or benzothiazole.
[0011] Photosensitizer: Photosensitizer can accelerate the degradation rate of materials under ultraviolet light. In this formula, the main function of the photosensitizer is to adjust the degradation time of the material, ensuring that the express bag maintains stable mechanical properties and waterproofness within a certain use cycle, and can degrade quickly after being discarded. Its mechanism is to absorb ultraviolet energy and trigger the breakage of polymer chains, thereby accelerating the degradation process of the material.
[0012] Preferably, the bio-enzyme catalyst comprises one of lipase or protease.
[0013] Bioenzyme catalyst: Bioenzyme catalyst can accelerate the hydrolysis process of materials under the action of microorganisms. Lipase and protease can catalyze the cleavage of ester bonds or peptide bonds in fatty acids and protein structures respectively, thereby promoting the hydrolysis and degradation of the matrix material. The addition of bioenzymes makes the degradation process more environmentally friendly, independent of chemical degradation agents, and can complete the degradation in a shorter time.
[0014] Preferably, the plasticizer comprises one of a citrate ester or a succinate ester.
[0015] Plasticizers: Plasticizers are used to improve the flexibility and processability of materials. By reducing the interaction between polymer chains, plasticizers can make materials softer and more ductile, adapting to the stretching and tearing that may be encountered during express transportation. In addition, plasticizers help reduce the temperature and pressure required during processing, improving production efficiency.
[0016] A method for preparing a waterproof express bag comprises the following steps: Mixing polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate to prepare a mixture; Adding a photosensitizer and a bio-enzyme catalyst into the mixture and mixing them; adding nanocellulose and modified montmorillonite into the mixture and mixing; adding a plasticizer to the mixture and mixing; extruding the mixture into a film; The film is heat pressed.
[0017] Preferably, the polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate are dried before mixing, and the drying temperature is 55-60° C. and the drying time is 4 hours.
[0018] Drying can ensure that polylactic acid (PLA), polybutylene adipate terephthalate (PBAT) and polyhydroxyalkanoate (PHA) are not disturbed by moisture during subsequent mixing and processing, and maintain their good physical properties and processing properties. The key role of this step is to avoid problems such as bubbles, decomposition or uneven mixing caused by the presence of moisture, thereby improving the quality and consistency of the final product.
[0019] Preferably, when the polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate are mixed, a shear mixer is used to stir them at a temperature of 170 to 180° C. and a rotation speed of 100 to 150 rpm for 10 to 20 minutes.
[0020] The strong mixing of the shear mixer ensures that different polymer materials are well dispersed and blended at the molecular level, avoiding material inhomogeneity. The temperature is controlled at 170-180℃ to avoid decomposition caused by overheating of the material and maintain good solubility.
[0021] Preferably, after the photosensitizer and the bio-enzyme catalyst are added, stirring is continued for 10 to 20 minutes at a temperature of 170 to 180° C. and a rotation speed of 100 to 150 rpm; The addition of photosensitizers and enzyme catalysts is to ensure that the bag has sufficient strength during use and can degrade quickly after being discarded by regulating the degradation rate. Photosensitizers can stimulate the degradation reaction of materials under ultraviolet light, while enzyme catalysts accelerate the degradation process of materials by promoting hydrolysis reactions.
[0022] After the nanocellulose and modified montmorillonite are added, stirring is performed for 20 to 25 minutes at a temperature of 170 to 180° C. and a rotation speed of 180 to 200 rpm; The introduction of nanocellulose increases the microstructure complexity of the material to improve its tensile strength and wear resistance, and improves the mechanical properties of the film. Modified montmorillonite, as a nanofiller, can improve the barrier properties of the material and reduce water penetration through filling.
[0023] After the plasticizer is added, stirring is performed for 10 to 15 minutes at a temperature of 170 to 180° C. and a rotation speed of 200 to 230 rpm.
[0024] Plasticizers make the material softer and more flexible by reducing the interaction between polymer molecular chains, thereby improving its ability to withstand pressure and stretching during actual transportation. The purpose of this step is to make the material have good flexibility and adaptability while maintaining high strength.
[0025] Preferably, when the film is extruded, a twin-screw extruder is used, the extrusion temperature is 170-180° C., the screw speed is 50-80 rpm, the extrusion speed is 20-40 m / min, and the film thickness is 0.05-0.1 mm.
[0026] The twin-screw extruder plays the role of melting, mixing and shaping in this step. Its strong mechanical action can ensure that the materials are fully mixed. At the same time, the temperature, pressure and other parameters can be adjusted during the extrusion process to obtain the ideal film thickness and physical properties.
[0027] Preferably, the hot pressing is carried out using a hot press machine at a temperature of 50 to 55° C. and a pressure of 2 to 4 MPa for 3 to 5 minutes.
[0028] During the hot pressing process, the film is made denser and its waterproof performance is enhanced by a certain temperature and pressure. By controlling the hot pressing temperature, pressure and time, the overall performance of the film can be effectively improved and its durability during transportation can be improved.
[0029] The present invention provides a courier waterproof bag and a preparation method thereof, which has the following beneficial effects: 1. The present invention significantly improves the biodegradability of the waterproof bag while ensuring the mechanical strength of the bag by combining polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate. PLA, as a bio-based degradable material, degrades mainly through hydrolysis to break the molecular chain and eventually decompose into carbon dioxide and water. The addition of PBAT and PHA can adjust the degradation rate of PLA so that it will not degrade prematurely during use, and can also ensure that the material can be quickly degraded after use. Compared with the solution of using only a single material in the prior art, the present invention optimizes the degradation rate to ensure the balance between material stability and environmental friendliness in actual use, thereby avoiding the problem of plastic pollution.
[0030] 2. The present invention uses nanocellulose and modified montmorillonite as fillers, and utilizes the high specific surface area and microstructure of nanocellulose to form a network structure in the polymer matrix, thereby significantly improving the tensile strength and crack resistance of the material. The introduction of modified montmorillonite increases the density of the material through its nanoscale particle size and layered structure, reduces the penetration of water, and plays an excellent waterproof role. Compared with traditional fillers, the nanomaterials of the present invention can be more evenly distributed in the matrix, ensuring the overall stability and durability of the waterproof bag, so that it can effectively protect the package from moisture during express transportation.
[0031] 3. The present invention reduces the interaction force between molecular chains by inserting plasticizers into the gaps between polymer molecules, thereby making the material softer and more extensible. This not only improves the tear resistance and service life of the express waterproof bag, but also reduces the processing temperature and pressure during the extrusion process, optimizes the production process, and compared with the materials in the prior art that do not use plasticizers, the present invention can maintain high strength while improving the flexibility of the material, making it more adaptable to the friction and external forces of express parcels during transportation.
[0032] 4. The present invention introduces photosensitizers and bio-enzyme catalysts. The photosensitizer can stimulate the degradation reaction of the material under ultraviolet irradiation, promote the breakage of polymer chains, and thus accelerate the degradation of the bag after it is discarded. The bio-enzyme catalyst can further accelerate the hydrolysis process of the material under the action of microorganisms, so that the material degrades faster in the natural environment. Compared with the existing technical solutions that only rely on chemical degradation or non-degradable plastic materials, the degradation system of the present invention can degrade quickly and efficiently after the end of the service life, reduce the burden on the environment, meet the needs of sustainable development, and improve the environmental friendliness of the material. DETAILED DESCRIPTION
[0033] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.
[0035] Example 1 Step 1: Prepare the ingredients Weigh 65 parts of polylactic acid (PLA), 25 parts of polybutylene adipate terephthalate (PBAT) and 8 parts of polyhydroxyalkanoate (PHA). Put all the raw materials into a drying oven and dry them at 55°C for 4 hours to ensure that the moisture in the raw materials is removed to avoid moisture affecting the mixing and subsequent processing performance.
[0036] Step 2: Base material mixing The dried PLA, PBAT and PHA were added into a shear mixer in proportion and stirred for 15 minutes at a temperature of 175° C. and a rotation speed of 120 rpm.
[0037] Step 3: Add photosensitizer and enzyme catalyst 1 part of photosensitizer (benzophenone) and 0.4 parts of bio-enzyme catalyst (lipase) were added to the mixture, and stirring was continued at 170° C. and 120 rpm for 18 minutes.
[0038] Step 4: Addition of nanocellulose and modified montmorillonite 2.5 parts of nanocellulose and 2 parts of modified montmorillonite were added, and the mixture was stirred at a temperature of 180° C. and a rotation speed of 180 rpm for 20 minutes.
[0039] Step 5: Add plasticizer Add 1 part of plasticizer citrate and continue stirring for 10 minutes.
[0040] Step 6: Film Extrusion The mixture was fed into a twin-screw extruder, and the set temperature was 175°C, the screw speed was 60 rpm, and the extrusion speed was 25 m / min. The film thickness was controlled at 0.08 mm.
[0041] Step 7: Heat Pressing Use a hot press machine to heat press for 5 minutes at 50°C and a pressure of 3MPa to make the film denser and improve its waterproofness and overall strength.
[0042] Example 2 Step 1: Prepare the ingredients 60 parts of polylactic acid (PLA), 30 parts of polybutylene adipate-terephthalate (PBAT) and 5 parts of polyhydroxyalkanoate (PHA) were selected and the material was dried at 55° C. for 4 hours to remove moisture.
[0043] Step 2: Mixing Process The three polymer materials were added into a shear mixer, the temperature was set to 170°C, the speed was set to 130 rpm, and the stirring was performed for 15 minutes.
[0044] Step 3: Add photosensitizer and enzyme catalyst 1.2 parts of photosensitizer (benzothiazole) and 0.3 parts of bio-enzyme catalyst (protease) were added to the mixture, and stirring was continued at 175° C. and 120 rpm for 10 minutes.
[0045] Step 4: Nanomaterial addition 3 parts of nanocellulose and 1.5 parts of modified montmorillonite were added, and stirred at 180° C. and 200 rpm for 22 minutes.
[0046] Step 5: Addition of plasticizer 1 part of plasticizer succinate was added and stirring was continued for 12 minutes to ensure uniform distribution of the plasticizer.
[0047] Step 6: Film Extrusion The mixture was extruded through a twin-screw extruder at a temperature of 175°C, a screw speed of 65 rpm, and an extrusion speed of 30 m / min to ensure that the film thickness was 0.07 mm.
[0048] Step 7: Heat Pressing The temperature in the hot press was set to 55°C, the pressure to 3 MPa, and the hot pressing time to 4 minutes to further enhance the density and waterproofness of the film.
[0049] Example 3 Step 1: Prepare the Ingredients Prepare 50 parts of polylactic acid (PLA), 35 parts of polybutylene adipate terephthalate (PBAT) and 7 parts of polyhydroxyalkanoate (PHA). Dry the raw materials at 55°C for 4 hours to ensure that moisture is removed.
[0050] Step 2: Base material mixing The dried PLA, PBAT and PHA were added into the shear mixer according to the proportion, the temperature was set to 175°C, the speed was 150 rpm, and the stirring was carried out for 15 minutes to allow the three materials to fully melt at high temperature to form a stable and uniform mixture.
[0051] Step 3: Addition of photosensitizer and enzyme catalyst Add 0.7 parts of photosensitizer benzophenone and 0.25 parts of bio-enzyme catalyst lipase, and continue stirring for 15 minutes.
[0052] Step 4: Adding nanocellulose and modified montmorillonite Add 2 parts of nanocellulose and 2 parts of modified montmorillonite, set the temperature to 180°C, the rotation speed to 200 rpm, and stir for 20 minutes.
[0053] Step 5: Add plasticizer Add 1 part of plasticizer citrate and continue stirring for 10 minutes.
[0054] Step 6: Film Extrusion The mixture was fed into a twin-screw extruder, and the temperature was set at 175°C, the screw speed was 60 rpm, and the extrusion speed was 25 m / min, ensuring that the film thickness was 0.08 mm.
[0055] Step 7: Heat Pressing The heat press was used for processing at 50°C, 3MPa and 4 minutes. The heat press process ensured the density of the material and improved its durability and waterproof performance.
[0056] Example 4 Step 1: Prepare the ingredients 62 parts of polylactic acid (PLA), 28 parts of polybutylene adipate terephthalate (PBAT) and 5 parts of polyhydroxyalkanoate (PHA) were selected and dried at 55° C. for 4 hours to remove moisture.
[0057] Step 2: Base Mixing Put all the dried raw materials into a shear mixer, set the temperature to 180°C, the speed to 130 rpm, and stir for 15 minutes.
[0058] Step 3: Add photosensitizer and enzyme catalyst 1.3 parts of photosensitizer (benzothiazole) and 0.3 parts of bio-enzyme catalyst (lipase) were added, and stirring was continued for 20 minutes.
[0059] Step 4: Adding Nanocellulose and Modified Montmorillonite Add 3 parts of nanocellulose and 2 parts of modified montmorillonite, set the stirring conditions to 180°C, 200 rpm, and stir for 25 minutes.
[0060] Step 5: Addition of plasticizer 0.9 parts of plasticizer citrate was added and stirring was continued for 10 minutes.
[0061] Step 6: Film Extrusion The material was fed into a twin-screw extruder, the extrusion temperature was set at 170°C, the screw speed was 55 rpm, and the extrusion speed was 30 m / min, ensuring that the film was uniform and reached a thickness of 0.06 mm.
[0062] Step 7: Heat Pressing The film was processed using a heat press with the temperature set at 55°C, the pressure at 3MPa, and the processing time at 4 minutes to ensure that the waterproof bag had excellent anti-permeability and mechanical strength.
[0063] Comparative Example 1 Step 1: Prepare the ingredients 30 parts of polybutylene adipate-terephthalate (PBAT) and 10 parts of polyhydroxyalkanoate (PHA) were selected. All raw materials were placed in a drying oven and dried at 55°C for 4 hours to ensure that the moisture in the raw materials was removed to avoid moisture affecting mixing and subsequent processing performance.
[0064] Step 2: Base material mixing The dried PBAT and PHA were added into a shear mixer in proportion and stirred for 15 minutes at a temperature of 175° C. and a rotation speed of 120 rpm.
[0065] Step 3: Add photosensitizer and enzyme catalyst 1 part of photosensitizer (benzophenone) and 0.4 parts of bio-enzyme catalyst (lipase) were added to the mixture, and stirring was continued at 170° C. and 120 rpm for 18 minutes.
[0066] Step 4: Addition of nanocellulose and modified montmorillonite 2.5 parts of nanocellulose and 2 parts of modified montmorillonite were added, and the mixture was stirred at a temperature of 180° C. and a rotation speed of 180 rpm for 20 minutes.
[0067] Step 5: Add plasticizer Add 1 part of plasticizer citrate and continue stirring for 10 minutes.
[0068] Step 6: Film Extrusion The mixture was fed into a twin-screw extruder, and the set temperature was 175°C, the screw speed was 60 rpm, and the extrusion speed was 25 m / min. The film thickness was controlled at 0.08 mm.
[0069] Step 7: Heat Pressing Use a hot press machine to heat press for 5 minutes at 50°C and a pressure of 3MPa to make the film denser and improve its waterproofness and overall strength.
[0070] Comparative Example 2 Step 1: Prepare the ingredients Select 65 parts of polylactic acid (PLA), 25 parts of polybutylene adipate terephthalate (PBAT) and 8 parts of polyhydroxyalkanoate (PHA). Put all the raw materials into a drying oven and dry them at 55°C for 4 hours to ensure that the moisture in the raw materials is removed to avoid moisture affecting the mixing and subsequent processing performance.
[0071] Step 2: Base material mixing The dried PLA, PBAT and PHA were added into a shear mixer in proportion and stirred for 15 minutes at a temperature of 175° C. and a rotation speed of 120 rpm.
[0072] Step 3: Add photosensitizer and enzyme catalyst 0.8 parts of photosensitizer (benzothiazole) and 0.2 parts of bio-enzyme catalyst (protease) were added to the mixture, and stirring was continued at 170° C. and 120 rpm for 18 minutes.
[0073] Step 4: Addition of nanocellulose and modified montmorillonite 2.5 parts of nanocellulose and 2 parts of modified montmorillonite were added, and the mixture was stirred at a temperature of 180° C. and a rotation speed of 180 rpm for 20 minutes.
[0074] Step 5: Add plasticizer Add 1 part of plasticizer citrate and continue stirring for 10 minutes.
[0075] Step 6: Film Extrusion The mixture was fed into a twin-screw extruder, and the set temperature was 175°C, the screw speed was 60 rpm, and the extrusion speed was 25 m / min. The film thickness was controlled at 0.08 mm.
[0076] Step 7: Heat Pressing Use a hot press machine to heat press for 5 minutes at 50°C and a pressure of 3MPa to make the film denser and improve its waterproofness and overall strength.
[0077] Comparative Example 3 Step 1: Prepare the ingredients Select 65 parts of polylactic acid (PLA), 25 parts of polybutylene adipate terephthalate (PBAT) and 8 parts of polyhydroxyalkanoate (PHA). Put all the raw materials into a drying oven and dry them at 55°C for 4 hours to ensure that the moisture in the raw materials is removed to avoid moisture affecting the mixing and subsequent processing performance.
[0078] Step 2: Base material mixing The dried PLA, PBAT and PHA were added into a shear mixer in proportion and stirred for 15 minutes at a temperature of 175° C. and a rotation speed of 120 rpm.
[0079] Step 3: Add photosensitizer and enzyme catalyst 1 part of photosensitizer (benzophenone) and 0.4 parts of bio-enzyme catalyst (lipase) were added to the mixture, and stirring was continued at 170° C. and 120 rpm for 18 minutes.
[0080] Step 4: Addition of nanocellulose and modified montmorillonite 1.5 parts of nanocellulose and 3 parts of modified montmorillonite were added, and stirred at a temperature of 180° C. and a rotation speed of 180 rpm for 20 minutes.
[0081] Step 5: Add plasticizer Add 1 part of plasticizer citrate and continue stirring for 10 minutes.
[0082] Step 6: Film Extrusion The mixture was fed into a twin-screw extruder, and the set temperature was 175°C, the screw speed was 60 rpm, and the extrusion speed was 25 m / min. The film thickness was controlled at 0.08 mm.
[0083] Step 7: Heat Pressing Use a hot press machine to heat press for 5 minutes at 50°C and a pressure of 3MPa to make the film denser and improve its waterproofness and overall strength.
[0084] Comparative Example 4 Step 1: Prepare the ingredients Select 65 parts of polylactic acid (PLA), 25 parts of polybutylene adipate terephthalate (PBAT) and 8 parts of polyhydroxyalkanoate (PHA). Put all the raw materials into a drying oven and dry them at 55°C for 4 hours to ensure that the moisture in the raw materials is removed to avoid moisture affecting the mixing and subsequent processing performance.
[0085] Step 2: Base material mixing The dried PLA, PBAT and PHA were added into a shear mixer in proportion and stirred for 15 minutes at a temperature of 175° C. and a rotation speed of 120 rpm.
[0086] Step 3: Add photosensitizer and enzyme catalyst 1 part of photosensitizer (benzophenone) and 0.4 parts of bio-enzyme catalyst (lipase) were added to the mixture, and stirring was continued at 170° C. and 120 rpm for 18 minutes.
[0087] Step 4: Addition of nanocellulose and modified montmorillonite 2.5 parts of nanocellulose and 2 parts of modified montmorillonite were added, and the mixture was stirred at a temperature of 180° C. and a rotation speed of 180 rpm for 20 minutes.
[0088] Step 5: Add plasticizer 1.5 parts of plasticizer citrate was added and stirring was continued for 10 minutes.
[0089] Step 6: Film Extrusion The mixture was fed into a twin-screw extruder, and the set temperature was 175°C, the screw speed was 60 rpm, and the extrusion speed was 25 m / min. The film thickness was controlled at 0.08 mm.
[0090] Step 7: Heat Pressing Use a hot press machine to heat press for 5 minutes at 50°C and a pressure of 3MPa to make the film denser and improve its waterproofness and overall strength.
[0091] Experiment 1 Experimental purpose: To verify the differences in degradation rate and mechanism between Example 1 and Comparative Example 1, focusing on observing the degradation process of the two under ultraviolet light and soil burial environments.
[0092] Experimental procedures Sample setup Example 1 Formulation: 65 parts PLA, 25 parts PBAT, 8 parts PHA Comparative Example 1: PBAT 30 parts, PHA 10 parts The number of samples in each group is 5 and the sample size is 10×10 cm.
[0093] Degradation test (UV irradiation) UV aging conditions: Use UV aging box, set wavelength to 365nm, irradiation intensity to 0.5W / m 2 , temperature 30℃, humidity 50%.
[0094] Take one sample every 7 days and record the sample quality, surface cracks and color changes.
[0095] After each sampling, the mass loss (weight change) was calculated, and the surface changes of the samples were recorded and photographed.
[0096] Degradation experiment (soil burial) Soil burial conditions: The samples were buried in standard laboratory soil with an organic matter content of 5% and a humidity of 40% at a depth of 20 cm and the temperature was maintained at 25 °C.
[0097] One piece was sampled every 14 days, and the mass loss was recorded after cleaning. The changes in the surface morphology of the sample were recorded by taking photos.
[0098] Test indicators Mass loss rate: The mass loss of the sample was calculated each time a sample was taken, and the formula was: (initial mass - current mass) / initial mass × 100%.
[0099] Morphology analysis: Scanning electron microscopy (SEM) was used to observe the cracks and holes on the sample surface.
[0100] Molecular weight change: Gel permeation chromatography (GPC) was used to test the molecular weight change of the sample and analyze the molecular chain breakage during the degradation process.
[0101] Data recording and analysis The mass loss data after each sampling was recorded, and SEM images were taken regularly to record the morphological changes.
[0102] The differences in the degradation process of different formulations were analyzed by statistical methods; Table 1: Degradation test data Experimental Summary In the ultraviolet light experiment, Example 1 showed a faster degradation rate. By 7 days, the mass loss rate of Example 1 was 12.3%, while that of Comparative Example 1 was only 5.6%. By 30 days, the mass loss rate of Example 1 significantly reached 38.9%, while that of Comparative Example 1 was 18.2%. This difference reflects the role of PLA in Example 1. The hydrolysis reaction of PLA accelerated the breakage of the molecular chain with the assistance of the photosensitizer, resulting in the rapid degradation of the material. PLA itself is more susceptible to photolysis under light conditions, which corresponds to the rapid development of surface cracks in Example 1. From the change in the level of surface cracks, the crack level of Example 1 was 4 (through cracks) at 30 days, while the crack level of Comparative Example 1 was only 2 (local short cracks). This difference shows that the addition of PLA accelerates the destruction of the surface structure of the material and enhances the degradation process.
[0103] In the soil burial experiment, Example 1 also showed a high degradation rate. The mass loss rate of Example 1 at 30 days was 23.6%, while that of Comparative Example 1 was 12.1%. This further proves that the addition of PLA accelerates the degradation process. The biodegradability of PLA is combined with PBAT and PHA in the soil environment to enhance the degradation performance. In particular, the molecular chain of PLA is more easily broken by hydrolysis, while PBAT and PHA provide additional degradation power during the decomposition process, making the degradation performance of Example 1 significantly better than that of Comparative Example 1.
[0104] The surface crack grade in Example 1 increased from Grade 2 (sporadic fine cracks) at 7 days to Grade 4 (through cracks) at 30 days, while the crack grade in Comparative Example 1 was only Grade 2. This indicates that the addition of PLA not only accelerated the degradation of the material under ultraviolet light conditions, but also promoted the degradation of microorganisms in the soil.
[0105] In summary, the experimental results clearly show that the addition of PLA in Example 1 significantly increases the degradation rate of the express waterproof bag. The synergistic effect of the hydrolysis characteristics of PLA and the photosensitizer effectively accelerates the degradation process of the material, which makes Example 1 superior to Comparative Example 1 in terms of environmental protection. Example 1 has excellent degradation performance under ultraviolet light and soil environment, which further proves the important role of PLA as a biodegradable material in the present invention.
[0106] Experiment 2: Comparison of the effects of photosensitizer and bio-enzyme catalyst on the degradation rate of express waterproof bags Purpose The effects of photosensitizer and bio-enzyme catalyst on the degradation rate of express waterproof bags were evaluated. The experiment compared the degradation performance differences between Example 2 (using benzothiazole photosensitizer and protease bio-enzyme catalyst) and Comparative Example 2 (not using photosensitizer and bio-enzyme catalyst).
[0107] Experimental procedures Sample selection: Example 2 Samples: 3 samples were selected from the formulation of Example 2 to ensure that the quality of each sample was consistent and in accordance with the corresponding formulation (the addition of benzothiazole photosensitizer and protease bio-enzyme catalyst).
[0108] Comparative Example 2 samples: 3 samples were selected from the formulation of Comparative Example 2, which did not contain a photosensitizer and a bio-enzyme catalyst.
[0109] Other formulation ingredients, preparation methods, and external dimensions of all samples should be identical to ensure that the test results are only affected by the photosensitizer and bio-enzyme catalyst.
[0110] Degradation test: Ultraviolet light experiment: The samples of Example 2 and Comparative Example 2 were exposed to ultraviolet light with a wavelength of 365nm, a temperature of 30°C, and a humidity of 50% to simulate the sunlight exposure environment. The mass change and surface morphology change (cracks, holes, discoloration, etc.) of each sample were recorded, and samples were taken every two weeks.
[0111] Soil burial experiment: The samples of Example 2 and Comparative Example 2 were buried in standard soil, respectively, with a soil moisture content of 40% and a temperature set at 25° C. Samples were taken every two weeks, and the mass changes were recorded, and cracks and surface changes were checked.
[0112] Data Records: Mass loss: After each sampling, the mass of the sample was accurately weighed using an electronic balance and the mass loss rate was calculated.
[0113] Surface morphology: Scanning electron microscopy (SEM) was used to analyze the surface cracks, holes and other changes of the samples.
[0114] Discoloration: Record the discoloration of the sample and evaluate it using a 0-5 scale.
[0115] Experimental setup: Three samples were tested in each group to ensure that each sample received the same treatment during the experiment.
[0116] The experiment lasted for 3 months, with samples taken every two weeks and data recorded regularly to ensure that the experimental data were representative.
[0117] Table 2: Mass loss and surface changes during degradation experiments (time unit: day) Experimental Summary According to the results of Experiment 2, Example 2 (adding photosensitizer benzothiazole and bio-enzyme catalyst protease) showed a significantly higher degradation rate under ultraviolet light and soil burial environment. In particular, under ultraviolet light conditions, the mass loss rate of Example 2 at 14 days was 13.2%, while that of Comparative Example 2 was only 5.3%. By 60 days, the mass loss rate of Example 2 reached 43.4%, while that of Comparative Example 2 was 21.6%. This obvious difference shows that the photochemical reaction of the photosensitizer benzothiazole under ultraviolet light promoted the degradation of the material, formed cracks and accelerated the breakage of the molecular chain.
[0118] In the soil burial experiment, the mass loss rate of Example 2 was also higher than that of Comparative Example 2. At 30 days, the mass loss rate of Example 2 was 18.9%, while that of Comparative Example 2 was 7.8%; at 60 days, the mass loss rate of Example 2 reached 28.1%, while that of Comparative Example 2 was 13.5%. This indicates that the bio-enzyme catalyst accelerated the hydrolysis of the material under the action of microorganisms, further increasing the degradation rate.
[0119] The grade and discoloration of the surface cracks also support this conclusion. The crack grade of Example 2 increased from Grade 2 (small cracks) at 14 days to Grade 4 (large cracks) at 60 days, while the crack grade of Comparative Example 2 only increased from Grade 1 (slight cracks) to Grade 2 (medium cracks). At the same time, the discoloration grade of Example 2 is also higher than that of Comparative Example 2, proving that the effects of the photosensitizer and the bio-enzyme catalyst accelerate the physical and chemical changes of the material.
[0120] In general, Example 2 significantly accelerated the degradation process of the material by introducing photosensitizers and bio-enzyme catalysts, especially under ultraviolet light and soil environments. Therefore, the effectiveness of photosensitizers and bio-enzyme catalysts in improving the environmental protection and degradation rate of express waterproof bags was verified.
[0121] Experiment 3: Evaluation of the improvement of waterproof performance of express waterproof bags by adding nanocellulose and modified montmorillonite Purpose The improvement of the waterproof performance of express waterproof bags by adding nanocellulose (CNF) and modified montmorillonite (MMT) additives was evaluated, and the difference in waterproof performance between Example 3 (adding 2.5 parts of nanocellulose and 2 parts of modified montmorillonite) and Comparative Example 3 (not adding nanocellulose and modified montmorillonite) was compared.
[0122] Experimental procedures Sample selection and preparation: Example 3 Samples: 3 samples were selected from the formulation of Example 3 to ensure that the quality and size of each sample were consistent. Each sample contained 2.5 parts of nanocellulose and 2 parts of modified montmorillonite.
[0123] Comparative Example 3 samples: Three samples were selected from the formulation of Comparative Example 3, ensuring that the quality and size of each sample were consistent, but excluding nanocellulose and modified montmorillonite.
[0124] The other formulation ingredients and processing techniques were kept the same for all samples.
[0125] Waterproof performance test: Water tightness test (according to GB / T4744-2006 standard): expose the sample to a certain pressure to simulate the pressure and moisture that the waterproof bag may encounter during actual transportation. Each sample is tested 3 times, and the time of water penetration and the amount of water permeation are recorded.
[0126] Water penetration time determination: Place each sample in a water tank, apply standard pressure, measure the time it takes for water to penetrate into the sample, and record the water penetration rate.
[0127] Data recording and analysis: Water penetration time: record the time of water penetration in each test, and compare the penetration difference between Example 3 and Comparative Example 3.
[0128] Water permeability: The water permeability of each group of samples is recorded to evaluate the impact of different additives on waterproof performance.
[0129] Experimental cycle: 3 samples were tested in each group to ensure the reliability and representativeness of the data.
[0130] Experimental setting Experimental environment: The experiment will be conducted at a temperature of 23°C and a relative humidity of 50% to ensure environmental consistency.
[0131] Number of samples: 3 samples per group.
[0132] Experimental period: The experiment will last for 3 months, with periodic tests and water penetration recorded after each test.
[0133] Table 3: Waterproof performance test data (water penetration time and water penetration) Experimental Summary It can be seen from the data that Example 3 exhibits better waterproof performance within the 3-month experimental period, with a short water seepage time and a small amount of water seepage. The water seepage time of Example 3 is 12 minutes at 30 days, 11 minutes at 60 days, and 13 minutes at 90 days, while the water seepage time of Comparative Example 3 is 20, 19, and 22 minutes, respectively, showing that the waterproof performance of Example 3 is significantly better than that of Comparative Example 3. In terms of water permeation, the water seepage of Example 3 at 90 days is 0.13 ml, which is less than 0.22 ml of Comparative Example 3, indicating that Example 3 has stronger waterproof ability after adding nanocellulose and modified montmorillonite.
[0134] This difference can be explained by the high surface area and filling effect of nanocellulose and modified montmorillonite. Nanocellulose forms a more compact network structure in the polymer matrix, reducing the penetration path of water; while the nanoparticles of modified montmorillonite further improve the barrier property of the material and enhance its waterproof performance. In contrast, the comparative example 3 without these two materials has a looser material structure and stronger water permeability when subjected to external force and water pressure.
[0135] In general, the experimental results clearly demonstrate the significant effect of nanocellulose and modified montmorillonite in improving the waterproof performance of express waterproof bags. By improving the structural stability and barrier properties of the material, Example 3 exhibited better water resistance during the experimental period and is suitable for packaging applications that require long-term and efficient waterproofing.
[0136] Experiment 4: Evaluating the effect of plasticizers on improving the flexibility and tensile strength of express waterproof bags Purpose The effect of the plasticizer (citrate ester) on improving the flexibility and tensile strength of the express waterproof bag was evaluated, and the flexibility and tensile strength of Example 4 (with the addition of citrate ester plasticizer) were compared with those of Comparative Example 4 (without the addition of plasticizer) under low and high temperature conditions.
[0137] Experimental procedures Sample selection and preparation: Example 4 samples: Select 3 samples from the Example 4 formulation, ensuring that each sample contains citrate plasticizer (1 part).
[0138] Comparative Example 4 samples: 3 samples were selected from the formula of Comparative Example 4, ensuring that each sample did not contain a plasticizer, and the other ingredients were the same as those of Example 4.
[0139] All samples should be kept consistent in size and shape to ensure comparability of experimental results.
[0140] Flexibility test: Bending test: Use a bending tester to test according to ASTM D1693 standard to evaluate the bending properties of each sample at -10°C and 50°C. Record the bending limit of the sample at both temperatures and whether cracks occur.
[0141] Low temperature tensile test: The tensile test is carried out at -10℃ to measure the tensile strength of the sample and record whether cracks or breaks occur.
[0142] Tensile strength test: High temperature tensile test: Use a standard tensile tester (GB / T1040.3-2018, ISO527-1:2019) to test the maximum tensile strength of each sample at 50°C, and record the tensile strength of the sample under high temperature conditions.
[0143] Room temperature tensile test: The tensile test was carried out at room temperature (23°C) to test the tensile strength and elongation of each sample.
[0144] Data recording and analysis: After each test, the tensile strength, flexural strength, elongation, crack occurrence, etc. of the sample were recorded.
[0145] At least 5 independent tests were performed to ensure the reliability and consistency of the data.
[0146] Experimental setting Experimental environment: The experiment will be carried out at a temperature of 23°C and a relative humidity of 50%. During the test, low-temperature and high-temperature tests will be carried out at -10°C and 50°C respectively.
[0147] Sample size: 3 samples were used in each experiment.
[0148] Experimental period: The experiment lasted for 3 months, with tests conducted once a month and the performance changes of the samples recorded after each test.
[0149] Table 4: Test data of plasticizers on flexibility and tensile strength Experimental Summary The plasticizer (citrate ester) of Example 4 significantly improves the flexibility and tensile resistance of the express waterproof bag. The data show that the bending limits of Example 4 at 30 days, 60 days and 90 days are higher than those of Comparative Example 4, especially at 90 days, the bending limit of Example 4 reaches 55°, while that of Comparative Example 4 is only 35°. This shows that the addition of plasticizer significantly enhances the flexibility of the material in a low temperature environment, enabling it to better resist external forces during transportation and reduce the occurrence of cracks.
[0150] At room temperature, the tensile strength of Example 4 is also significantly higher than that of Comparative Example 4. At 30 days, the room temperature tensile strength of Example 4 is 19.4 MPa, while that of Comparative Example 4 is 15.2 MPa. As time goes by, the tensile strength of Example 4 remains at a high level at 60 days and 90 days, while that of Comparative Example 4 gradually decreases. This shows that the plasticizer not only improves the initial strength of the material, but also delays the decline in strength of the material in long-term use.
[0151] Most notably, under low temperature conditions, the tensile strength of Example 4 is significantly better than that of Comparative Example 4. In the test at -10°C, the tensile strengths of Example 4 are 10.3MPa, 11.2MPa and 12.0MPa, respectively, while the tensile strengths of Comparative Example 4 at the same time points are lower, 7.4MPa, 8.1MPa and 8.9MPa, respectively. The plasticizer enables the material to maintain high tensile strength and toughness at low temperatures, and can effectively avoid cracks and fractures in low temperature environments.
[0152] The addition of plasticizers increases the flexibility of the material and improves its tensile properties in high and low temperature environments. By reducing the interaction between polymer molecules, plasticizers enhance the softness and ductility of the material, which is of great significance to the adaptability and durability of express waterproof bags during transportation.
[0153] Experiment 5: Comparison of the comprehensive effects of different polymer formulations on the mechanical properties and degradability of express waterproof bags Purpose The comprehensive effects of different polymer formulas on the mechanical properties and degradability of express waterproof bags were compared, and the performance of Example 1 (65 parts of PLA, 25 parts of PBAT, 8 parts of PHA), Example 2 (60 parts of PLA, 30 parts of PBAT, 10 parts of PHA), Comparative Example 1 (30 parts of PBAT, 10 parts of PHA) and Comparative Example 2 (no biodegradable materials were used) in terms of mechanical properties, degradation rate and waterproof performance were evaluated.
[0154] Experimental procedures Sample selection and preparation: Samples of Example 1: 3 samples of Example 1 were selected, and the samples contained PLA, PBAT, and PHA in a certain proportion.
[0155] Samples of Example 2: 3 samples of Example 2 were selected, and the samples contained PLA, PBAT, and PHA in a certain proportion.
[0156] Comparative Example 1 samples: 3 samples of Comparative Example 1 were selected, and the samples contained PBAT and PHA.
[0157] Comparative Example 2 samples: 3 samples of Comparative Example 2 were selected, without using biodegradable materials (containing only PBAT).
[0158] The size, thickness and preparation method of all samples were kept consistent.
[0159] Mechanical properties test: Tensile strength test: A tensile strength tester (GB / T1040.3-2018, ISO527-1:2019) was used to test the tensile strength of each group of samples to determine the maximum tensile strength of the samples.
[0160] Tear resistance test: According to the standard tear test method (ISO6383), the tear resistance of each sample was tested.
[0161] Degradation test: UV light degradation test: The samples were exposed to a UV light source with a wavelength of 365nm and an intensity of 0.5W / m 2 , the temperature was set at 30℃ and the humidity was 50% to simulate the sunlight exposure environment. The mass loss of the samples was recorded every two weeks.
[0162] Soil burial degradation test: bury the samples in standard soil with a humidity of 40% and a temperature of 25°C. Take samples every two weeks and record the mass loss and morphological changes of the samples.
[0163] Waterproof performance test: Water tightness test: According to the water tightness test method of GB / T4744-2006, the waterproof performance of the sample is evaluated and the time and amount of water penetration are recorded.
[0164] Data recording and analysis: Mechanical properties data: The maximum tensile strength and tear strength of each sample were recorded.
[0165] Degradation data: Record the mass loss of each group of samples in UV irradiation and soil burial experiments.
[0166] Waterproof performance data: record the water penetration time and amount of each group of samples.
[0167] Experimental setup Experimental environment: All experiments will be conducted in an environment with a temperature of 23°C and a relative humidity of 50%.
[0168] Number of samples: 3 samples per group.
[0169] Experimental period: The experimental period is 3 months, with sampling and testing every 30 days.
[0170] Table 5: Comprehensive performance test data (mechanical properties, degradation rate and waterproof performance) Experimental Summary According to the results of Experiment 5, Examples 1 and 2 are superior to Comparative Examples 1 and 2 in terms of mechanical properties, degradation rate and waterproof performance. In particular, in terms of tensile strength and tear strength, the performances of Examples 1 and 2 are relatively outstanding. At 30 days, the tensile strength of Example 1 was 19.4 MPa and the tear strength was 25.6 N, while the tensile strength of Comparative Example 1 was 15.2 MPa and the tear strength was 18.5 N. At 90 days, the tensile strength of Example 1 increased to 21.5 MPa and the tear strength reached 35.0 N.
[0171] In the degradation test, the UV light mass loss rate and soil burial mass loss rate of Example 1 and Example 2 were higher than those of Comparative Example 1 and Comparative Example 2, proving that the biodegradation characteristics of PLA and PHA effectively accelerated the degradation process of the materials. The UV light mass loss rate of Example 1 reached 38.9% at 90 days, while that of Comparative Example 2 was only 10.1%.
[0172] In terms of waterproof performance, the water penetration time and water seepage amount of Examples 1 and 2 are significantly lower than those of Comparative Examples 1 and 2, indicating that the reasonable combination of PLA, PBAT and PHA enhances the water tightness of the waterproof bag. The water seepage time of Example 1 is 10 minutes and the water seepage amount is 0.09 ml, while the water seepage time of Comparative Example 2 is 25 minutes and the water seepage amount is 0.22 ml.
[0173] The experimental results show that Example 1 and Example 2 are superior in comprehensive performance, especially in the improvement of mechanical properties, degradation rate and waterproof performance, which proves the advantages of PLA and PHA as biodegradable materials.
[0174] Embodiment 5: In this embodiment, the editable QR code is directly printed on the express waterproof bag, and the surface of the waterproof bag is used as the QR code information carrier, which not only improves the convenience of using the QR code, but also does not affect the original function of the waterproof bag. The specific operation is as follows: Editable QR code design: An editable QR code is a QR code that can be updated with information through a dedicated QR code scanning device or related apps. Unlike traditional QR codes, its information is not fixed, but can be modified or updated at different stages of logistics transportation.
[0175] The QR code printed on the waterproof bag has a back-end system connected to a cloud platform or enterprise database, which can update the information in the QR code at the logistics node, such as the current status of the express, the delivery address, the shipping information, etc.
[0176] Printing Technology: Using specialized QR code printing technology, editable QR codes are printed directly on the surface of waterproof bags. Waterproof ink or special printing processes are used during the printing process to ensure that the QR code remains clear and scannable during transportation.
[0177] Since express waterproof bags usually need to withstand harsh transportation environments, the printing of QR codes needs to be highly water-resistant and abrasion-resistant. By using high-quality printing materials, it is ensured that the QR code can maintain its clarity and scannability even when the surface of the waterproof bag is rubbed or exposed to a humid environment.
[0178] Combination of waterproof bag functionality and QR code application: The express waterproof bag itself has the characteristics of waterproof, wear-resistant, tear-resistant, etc., and the design and printing of the QR code will not affect the basic functions of the waterproof bag. The QR code is printed through a special waterproof treatment process to ensure that it will not be damaged or faded in a humid environment.
[0179] Users or logistics personnel can quickly obtain the logistics status or contact information of express packages by scanning the QR code. At the same time, when necessary, they can modify the QR code content through the QR code editing platform to cope with address changes, transportation route adjustments, etc.
[0180] Integration of intelligent logistics system: Through the real-time update of the QR code, express delivery companies can achieve full tracking of packages and even update dynamic information during the delivery process to improve logistics efficiency.
[0181] At the same time, consumers can also scan the QR code to obtain personalized information related to express delivery, such as estimated delivery time, transportation status, etc., to further enhance the user experience.
[0182] Application scenarios: Applicable to all express parcels that require rapid logistics tracking and management, especially those that require multiple changes in delivery information.
[0183] It can be widely used in e-commerce platforms, international express delivery, special commodity transportation and other scenarios to improve overall logistics efficiency and accuracy.
[0184] Effects of the embodiments Improve logistics efficiency: The introduction of editable QR codes allows express parcel information to be adjusted in real time during the delivery process, reducing delivery errors or delays caused by untimely information updates.
[0185] Enhanced consumer experience: By scanning the QR code, consumers can obtain real-time information on the status and logistics of the package, which enhances the interactivity and transparency of the shopping process.
[0186] Improve the intelligent functions of waterproof bags: By printing the QR code directly on the waterproof bag, the additional functions of the traditional packaging bag are improved, so that the traditional express bag has the function of a modern information carrier while maintaining the basic functions such as waterproof and durable. Therefore, through the implementation of the above technical solution, not only the intelligent function is added to the express waterproof bag, but also the flexibility and efficiency of logistics management are improved.
[0187] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A waterproof express bag, characterized in that: Includes the following mass ratio components: Polylactic acid: 60-70 parts Polybutylene adipate-terephthalate: 20-30 parts Polyhydroxyalkanoate: 5-10 parts Nanocellulose: 2-5 parts Modified montmorillonite: 1-3 parts Photosensitizer: 0.5-1.5 parts Bio-enzyme catalyst: 0.25-0.5 parts Plasticizer: 0.5 to 1 part.
2. The express waterproof bag according to claim 1, characterized in that: The photosensitizer includes one of benzophenone or benzothiazole.
3. The express waterproof bag according to claim 1, characterized in that: The biological enzyme catalyst includes one of lipase or protease.
4. The waterproof express bag according to claim 1, characterized in that: The plasticizer includes one of a citrate ester or a succinate ester.
5. A method for preparing a waterproof express bag, based on the waterproof express bag according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate to prepare a mixture; Adding a photosensitizer and a bio-enzyme catalyst into the mixture and mixing them; adding nanocellulose and modified montmorillonite into the mixture and mixing; adding a plasticizer to the mixture and mixing; extruding the mixture into a film; The film is heat pressed.
6. The method for preparing a waterproof express bag according to claim 5, characterized in that: The polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate are dried before mixing, the drying temperature is 55-60° C., and the drying time is 4 hours.
7. The method for preparing a waterproof express bag according to claim 5, characterized in that: When the polylactic acid, polybutylene adipate-terephthalate and polyhydroxyalkanoate are mixed, a shearing mixer is used to stir for 10 to 20 minutes at a temperature of 170 to 180° C. and a rotation speed of 100 to 150 rpm.
8. The method for preparing a waterproof express bag according to claim 7, characterized in that: After the photosensitizer and the bio-enzyme catalyst are added, stirring is continued for 10 to 20 minutes at a temperature of 170 to 180° C. and a rotation speed of 100 to 150 rpm; After the nanocellulose and modified montmorillonite are added, stirring is performed for 20 to 25 minutes at a temperature of 170 to 180° C. and a rotation speed of 180 to 200 rpm; After the plasticizer is added, stirring is performed for 10 to 15 minutes at a temperature of 170 to 180° C. and a rotation speed of 200 to 230 rpm.
9. The method for preparing a waterproof express bag according to claim 5, characterized in that: When the film is extruded, a twin-screw extruder is used, the extrusion temperature is 170-180° C., the screw speed is 50-80 rpm, the extrusion speed is 20-40 m / min, and the film thickness is 0.05-0.1 mm.
10. The method for preparing a waterproof express bag according to claim 5, characterized in that: The hot pressing is performed using a hot press machine at a temperature of 50 to 55° C. and a pressure of 2 to 4 MPa for 3 to 5 minutes.
Citation Information
Cited By
Environment-friendly degradable plastic material and preparation method thereof
CN120699404A
Environment-friendly insulating material for cable and preparation method of environment-friendly insulating material
CN121950007A
Biodegradable packaging film and preparation method thereof
CN122080605A